Removal of 2,4-Dichlorophenoxyacetic Acid from Aqueous Solutions Using Al2O3/Graphene Oxide Granules Prepared by Spray-Drying Method - Alexandra Yu. Kurmysheva; Ekaterina Kuznetsova; Marina D. Vedenyapina; Pavel Podrabinnik; Nestor Washington Solís Pinargote; Anton Smirnov; Sergey N. Grigoriev (Resources, 2024)
Within this study, aluminum oxide granules with 0.25%vol. of graphene oxide were prepared by a spray-drying method to make an adsorbent for the 2,4-Dichlorophenoxyacetic acid (2,4-D) herbicide removal from aqueous solutions. The obtained adsorbent was studied using infrared spectroscopy, scanning electron microscopy and Raman spectroscopy. The presence of graphene in the spray-dried powder was confirmed. The adsorption removal of 2,4-D using the obtained material was performed at an ambient temperature by varying the process parameters such as pH and adsorption time. The adsorption of 2,4-D was a monolayer chemisorption according to the Langmuir isotherm pattern and a pseudo-second-order kinetic model. The maximum Langmuir adsorption capacity of the monolayer was 35.181 mg/g. The results show that the Al2O3-0.25%vol. GO powder obtained by spray drying is suitable for the production of adsorbents for toxic herbicides.